Sobre a necessidade de uma dedução transcendental no âmbito da razão prática em Kant - Machado, Thomas Matiolli [UNESP] (2015)
This work has two objectives. The first one is to clarify what is the problem of the application of practical reason and why a transcendental deduction is necessary to deal with the problem. The second objective is to defend that the deduction held in the Groundwork for the metaphysics of morals is not necessary, even though a deduction, in the scope of practical reason, in general, is necessary. According to this view, one can expect to have greater clarity about the reasons why it is still necessary to support the application of practical reason, however, upon new perspectives, that is, by means of a new transcendental deduction which does not follow the paths open by the original one.